Pengaruh Persepsi Konsumen Dan Brand Positioning Terhadap Keputusan Pembelian Produk Kopi Kapal Api Di Toko Tujuh Empat Kota Malang - Rafi Achmad Ramadhani; Asminah Rachmi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Consumer perception is a process in the senses owned by consumers until a certain impression is formed subjectively. Each consumer has a unique perception value and is different from one another. In addition to consumer perception factors, companies also need to consider brand positioning to increase the buying decision. Brand positioning is the extent to which a brand is perceived to occupy a beneficial, different, unique, and credible position in the minds of consumers. Kapal Api was established to provide various types of coffee consumed by the community. Toko Tujuh Empat is one of the stores that provide products from Kopi Kapal Api. This study aims to find out how much influence consumer perception and brand positioning have on buying decision in Kapal Api Coffee products at Toko Tujuh Empat Malang City. This study used quantitative research with consumer perception variables. brand positioning, and buying decision. The purposive sampling technique was used as a data collection technique through a questionnaire and as many as 100 people as respondents. Meanwhile, the data analysis method used multiple linear regression analysis with classical assumption test, hypothesis test, and determination coefficient analysis. Based on the results of hypothesis testing both proportionally and simultaneously, it showed that consumer perception and brand positioning have a positive and significant influence on the buying interest of Kapal Api Coffee products at the Tujuh Empat store in Malang City. Based on the results of the research, it can be concluded that consumer perception and brand positioning are one of the reasons to influence purchasing decisions. Good consumer perception and brand positioning will improve purchasing decisions. Therefore, it is recommended that Kopi Kapal Api continue to improve the quality of its products in order to create purchasing decisions from consumers.